Conceptualizing environmental literacy and factors affecting pro-environmental behaviour - Wong, Charmaine Andrea; Mohammad Afandi, Syamsul Herman; Ramachandran, Sridar; Kunasekaran, Puvaneswaran; Chan, Jennifer Kim Lian (Universiti Malaysia Sarawak, 2018)
Environmental problems today are global in nature, requiring young and old alike to behave pro-environmentally in order to rectify environmental problems and prevent new problems from occurring. Environmentally literate individuals possess the knowledge and skills required to analyze environmental issues, which would enable the individual to behave pro-environmentally. The purpose of this study is to design a conceptual framework that links environmental literacy and factors affecting pro-environmental behaviour. Firstly, the development in formal and non-formal Environmental Education, within Malaysia and internationally are reviewed. This is followed by a review on Environmental Literacy over the past three decades, after which the concept of pro-environmental behaviour and relevant theories of behaviour are compared. The development of Environmental Education in Sabah and Malaysia, as well as the challenges faced between environmental sustainability and development in the tourism sector of Sabah, is then discussed. A conceptual framework that links environmental literacy and pro-environmental behaviour, for use among primary school students is proposed. This conceptual framework allows Environmental Education providers, curriculum developers and policy makers, to better understand the components within environmental literacy and the factors that need to be considered when providing and assessing current Environmental Education programs and interventions. Effective use of the framework will allow Environmental Education programs to be more effective in improving environmental literacy.